Extended fetal echocardiographic examination for detecting cardiac malformations in low risk pregnancies. Issue 6828 (14th March 1992) - Achiron, R.; Glaser, J.; Gelernter, I.; Hegesh, J.; Yagel, S.
Abstract : OBJECTIVE--To improve the rate of prenatal detection of cardiac malformations in a low risk population. DESIGN--Comparison of extended fetal echocardiography with the standard four chamber view in detecting abnormalities. Extended echocardiography comprised the four chamber view and visualisation of the left ventricular outflow tract, the right ventricular outflow tract, and the main pulmonary artery and its branches. In cases with abnormal results complete echocardiographic studies were performed by a paediatric cardiologist using M mode, Doppler, and colour flow mapping techniques. SETTING--Obstetric ultrasonographic unit at Shaare-Zedek Medical Centre, Jerusalem. SUBJECTS--5400 fetuses in low risk pregnancies between 18 and 24 weeks' gestation (mean 21 weeks); 53 were lost to follow up. MAIN OUTCOME MEASURES--Detection of abnormality before and after birth. RESULTS--During the study 23 infants (0.4%) were born with cardiac abnormalities, 21 of whom had major structural and functional heart disease. 18 fetuses had heart disease diagnosed prenatally, 11 by the four chamber view alone (sensitivity 48%) and a further seven by extended echocardiography (sensitivity 78%). Five fetal cardiac defects were missed prenatally (false negative rate 22%). These included coarctation of aorta, persistent truncus arteriosus, tetralogy of Fallot, ventricular septal defect, and pulmonic stenosis. Only one false positive diagnosis (coarctation of aorta) was made (specificity 99.9%, false positive rate 0.1%). The abnormality was correctly identified in 17 out of 18 cases. CONCLUSIONS--The extended fetal heart examination detected 86% (18/21) of major abnormalities in a low risk population. The examination should be incorporated into routine prenatal ultrasonographic investigations.